Fear of Missing Out in an Online Context and Dysfunctional Risks in Adolescents - Ortega-Barón, Jessica; González-Cabrera, Joaquín; Díaz-López, Adoración; Escortell-Sánchez, Raquel; Arroyo-González, María José; Machimbarrena, Juan Manuel (Human Behavior and Emerging Technologies, 2026)
Fear of missing out (FoMO) is a problematic kind of attachment related to the distress caused by knowing that others are having rewarding experiences of which one is not a part. Although this feeling can negatively impact the lives of adolescents, the relationship between FoMO and other risks of dysfunctional use of the Internet in this age range is little explored. Furthermore, there is a gap in the online FoMO assessment instruments for this age bracket. Therefore, the primary objective of this study was to evaluate the relationships between FoMO and problematic social networking site (PSNS) usage, nomophobia, and Internet gaming disorder (IGD). A secondary objective was to validate the Fear of Missing Out in the Online Context in Adolescent (FoMO-OA) scale. Differences according to sex and academic course were also analysed. An instrumental, analytical, and cross-sectional study was conducted with 3569 students aged 11–14 years (1794 males, 50.3%). The results indicate significant and positive relationships between FoMO, PSNS, nomophobia, and IGD. Users of social networks experienced significantly more FoMO (p < 0 001). Moreover, the FoMO-OA was validated with sufficient guarantees of validity and reliability. We obtained higher scores for girls and students in higher grades (p < 0 001). These results are particularly interesting for future prevention programs and parental online mediation strategies.
Keywords: adolescence; fear of missing out; Internet; risks; social networks